Stanzaic Syntax in the Madrashe of Ephrem the Syrian - Stevenson, Paul (Monographs of the Peshitta Institute, 2015)
In Stanzaic Syntax in the Madrashe of Ephrem the Syrian , which focuses on madrāšê V and VI in the Paradise cycle, Paul S. Stevenson looks at Ephrem's poetic art from the point of view of a linguist. This study goes beyond the traditional levels of analysis, the clause and the sentence, and examines the structure of whole stanzas as units. The result is a surprisingly rich tapestry of syntactic patterning, which can justly be considered the key to Ephrem's prosody. The driving force behind Ephrem's poetry turns out not to be meter or sound play, but a variety of syntactic templates, which include even vertical patterning of constituents.